Regional Innovation: Regional Leadership in Empowering the Aceh Community during the Covid-19 Pandemic - Agatha Debby Reiza Macella (Iapa Proceedings Conference, 2020)
Leadership is an important factor that we cannot avoid from the success of community empowerment in an area. Apart from the role of regional leadership that supports all innovations and creativity in society. Aceh Province has great potential to develop superior commodities such as coffee, patchouli, rattan, fisheries, potential for natural beauty and culture. The Covid-19 pandemic which infected almost all regions in and had a significant impact on economic conditions both at the central and regional levels, including in the province of Aceh. This research examines the extent of the role of regional leadership in empowering the people of Aceh during the Covid-19 pandemic and seeing what are the factors that affect regional leadership in empowering the community. The research method used is a descriptive qualitative approach and uses library research techniques. The results of his research show that regional leaders play a role as policy makers, coordinate and communicate with various related parties, carry out empowerment, monitor, and evaluate. Factors that influence internally: personal awareness of the duties and responsibilities of leaders, strong commitment, clarity of division of tasks, good communication between actors. External factors: The existence of local potential that should be empowered, the existence of joint commitment from the private sector, village government, universities and the community, the existence of positive support and acceptance and the economic and social conditions at that time.